Social aspects of Code-Switching: An analysis of Pakistani Television advertisements - Khan, Aalia Mehar (Information Management and Business Review, 2014)
Code switching is the shift from one language to the other or use of more than one language during conversations or writings. The present research deals with intra-sentential (within one sentence) code switching in the language of television advertisements. To facilitate the socio-linguistic analysis, 12 advertisements of beauty and health care products have been recorded and transcribed from four television channels. The linguistic analysis focuses on the social aspect (gender, geographical background, socioeconomic class, and education) of code switched language in these advertisements. From the analysis and findings, it is concluded the language of advertisements for beauty and health care products reflects a change in linguistic practices and preferences of Pakistani consumers.